Urogenital Schistosomiasis among Schoolchildren and the Associated Risk Factors in Selected Rural Communities of Kwara State, Nigeria - Babamale Olarewaju Abdulkareem; Kolawole Olasunkanmi Habeeb; Abdulganiyu Kazeem; Abdulkareem Olaitan Adam; Ugbomoiko Uade Samuel (Journal of Tropical Medicine)
Urogenital schistosomiasis is a chronic parasitic disease that causes severe morbidity among schoolchildren in many poor-resource communities in Nigeria. We investigated the prevalence, intensity, and risk factors of the infection in three communities of Kwara State to ascertain the current status of the disease. Of the 724 urine samples screened, using filtration method, 332 (45.6%) school-aged children were infected with average intensity and mean population eggs load of 127.9 eggs/10 ml of urine and 0.794, respectively. Prevalence and intensity of infection varied with communities: high in Ajase-Ipo (57.1%; X = 100.7 ± 23.01 eggs/10 ml) and low in Shonga (37.5%; X = 91.4 ± 78.0). Infection was significantly (P<0.05) higher in males (50.8%) than the females (42.4%). Similarly, infection significantly (P<0.05) increased with increasing age. Multivariate logistic analysis of risk factors revealed that lack of portable drinking water (adjusted odd ratio (aOR) = 4.76; 95% CI = 2.64–5.98), unemployment (aOR = 2.23; 1.87–2.294), lack of knowledge of infection (aOR = 2.16; 0.59–3.83), and frequent contact with contaminated water bodies (aOR = 2.01; 1.45–2.70) were important predictors of urinary schistosomiasis. Therefore, continuous evaluation of the intervention strategies that address risk factors must compliment Mass Drug Administration to curtail the transmission and debilitating health consequences of infection in endemic settings.